The Elachista dispunctella (Duponchel) complex (Lepidoptera, Elachistidae) revisited, with exceptional level of synonymy - Kaila, Lauri (Zootaxa, 2015)
The E. dispunctella and E. triseriatella complexes sensu Traugott-Olsen are merged. The newly delineated E. dispunctella complex is re-defined and diagnosed. Until now, a total of 64 species has been assigned to this species complex. The taxonomy of the constituent species has been obscure owing to their identities based on unvalidated traits, in particular subtle differences on branching points of forewing veins. The taxonomy of the E. dispunctella complex is revised on the basis of new material, new and reevaluated information obtained from morphology and biology, as well as from the standard barcode region of COI, with at least partial barcode data derived from 194 recently collected specimens and 33 holotypes. As a result, the number of species considered valid is markedly reduced, with only 19 species now recognized. The following 43 new synonymies are established: Elachista dispunctella (Duponchel, 1843) = E. cahorsensis Traugott-Olsen, 1992, syn. nov., E. imbi Traugott-Olsen, 1992, syn. nov., E. karsholti Traugott-Olsen, 1992, syn. nov., E. mannella Traugott-Olsen, 1992, syn. nov., E. multipunctella Traugott-Olsen, 1992, syn. nov., E. pocopunctella Traugott-Olsen, 1992, syn. nov., E. povolnyi Traugott-Olsen, 1992, syn. nov., E. punctella Traugott-Olsen, 1992, syn. nov., E. hallini Traugott-Olsen, 1992, syn. nov., E. intrigella Traugott-Olsen, 1992, syn. nov., E. skulei Traugott-Olsen, 1992 and E. nielspederi Traugott-Olsen, 1992, syn. nov.; E. tribertiella Traugott-Olsen, 1985 = E. toveella Traugott-Olsen, 1985, syn. nov., E. baldizzonella Traugott-Olsen, 1985, syn. nov., E. veletaella Traugott-Olsen, 1992, syn. nov., E. bazaella Traugott-Olsen, 1992, syn. nov. and E. louiseae Traugott-Olsen, 1992, syn. nov.; E. parvula Parenti, 1978 = E. minusculella Traugott-Olsen, 1992, syn. nov. and E. blancella Traugott-Olsen, 1992, syn. nov.; E. maboulella Chrétien, 1915 = E. catalunella Traugott-Olsen, 1992, syn. nov., E. gerdmaritella Traugott-Olsen, 1992, syn. nov. and E. gielisi Traugott-Olsen, 1992, syn. nov.; E. glaseri Traugott-Olsen, 1992 = E. rikkeae Traugott-Olsen, 1992, syn. nov., E. totanaensis Traugott-Olsen, 1992, syn. nov., E. olemartini Traugott-Olsen, 1992, syn. nov., E. bengtssoni Traugott-Olsen, 1992, syn. nov., E. senecai Traugott-Olsen, 1992, syn. nov., E. wadielhiraensis Traugott-Olsen, 1992, syn. nov., E. rissaniensis Traugott-Olsen, 1992, syn. nov. and E. michelseni Traugott-Olsen, 1992, syn. nov.; E. hispanica Traugott-Olsen, 1992 = E. vivesi Traugott-Olsen, 1992, syn. nov., E. cuencaensis Traugott-Olsen, 1992, syn. nov., E. vanderwolfi Traugott-Olsen, 1992, syn. nov., E. amparoae Traugott-Olsen, 1992, syn. nov., E. varensis Traugott-Olsen, 1992, syn. nov., E. luqueti Traugott-Olsen, 1992, syn. nov., E. occidentella Traugott-Olsen, 1992, syn. nov. and E. clintoni Traugott-Olsen, 1992, syn. nov.; E. berndtiella Traugott-Olsen, 1985 = E. casascoensis Traugott-Olsen, 1992, syn. nov.; E. triseriatella Stainton, 1854 = E. contisella Chrétien, 1922, syn. nov., E. gregori Traugott-Olsen, 1988, syn. nov., and E. lerauti Traugott-Olsen, 1992, syn. nov.; E. elsaella Traugott-Olsen, 1988 = E. svenssoni Traugott-Olsen, 1988, syn. nov.; E. galactitella (Eversmann, 1844) = E. madridensis Traugott-Olsen, 1992, syn. nov. E. deresyensis Traugott-Olsen, 1988 is resurrected as a valid species, stat. rev. Evidence from DNA barcodes suggests that there may exist further species, but in the absence of distinct morphological differences, they are not formally described as new.